2017
DOI: 10.1128/jvi.00668-17
|View full text |Cite
|
Sign up to set email alerts
|

Species Specificity of Vaccinia Virus Complement Control Protein for the Bovine Classical Pathway Is Governed Primarily by Direct Interaction of Its Acidic Residues with Factor I

Abstract: Poxviruses display species tropism-variola virus is a human-specific virus, while vaccinia virus causes repeated outbreaks in dairy cattle. Consistent with this, variola virus complement regulator SPICE (smallpox inhibitor of complement enzymes) exhibits selectivity in inhibiting the human alternative complement pathway and vaccinia virus complement regulator VCP (vaccinia virus complement control protein) displays selectivity in inhibiting the bovine alternative complement pathway. In the present study, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…Thus, it is possible that poxviruses whose E3 orthologs inhibit PKR less efficiently might depend more on their K3 orthologs for PKR inhibition than is currently recognized. Similarly, orthologs of the complement-binding factor VCP from VACV, VARV and MPXV were shown to inhibit complement factors in a species-specific manner [ 33 37 ]. Another example of variations in poxviral immune antagonist activity is found in the poxvirus C7L family, which confers host range function in different poxviruses [ 38 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that poxviruses whose E3 orthologs inhibit PKR less efficiently might depend more on their K3 orthologs for PKR inhibition than is currently recognized. Similarly, orthologs of the complement-binding factor VCP from VACV, VARV and MPXV were shown to inhibit complement factors in a species-specific manner [ 33 37 ]. Another example of variations in poxviral immune antagonist activity is found in the poxvirus C7L family, which confers host range function in different poxviruses [ 38 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Site-directed mutagenesis performed to probe the structural basis of this specificity indicated that charge dictates the species specificity in poxviral complement regulatorspositively charged residues (K108 and K120) impart specificity towards the human complement, and negatively charged (E108, E120 and E144) residues direct the specificity towards the bovine complement. Further, it was also revealed that these residues are directly involved in the interaction with FI [129,130].…”
Section: Structure-function Relationship Of Viral Rcamentioning
confidence: 93%
“…Like most proteins, functional sites were present on the external face of the proteins. Site-directed mutagenesis studies performed in pox (VCP and SPICE) [118, [129][130][131] and herpesviral (HVS CCPH and Kaposica) [98,120,122] RCA proteins have identified multiple sites critical for DAA and CFA. These data, together with the information on functional sites in huRCA, provided a wealth of knowledge on the structure-function relationship.…”
Section: Structure-function Relationship Of Viral Rcamentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the species specificity of SPICE and VCP showed that both exhibit strong selectivity, which is consistent with the species tropism of variola and vaccinia viruses, i.e., SPICE is human complement specific and VCP bovine complement specific. Remarkably, the determinant for the switch in the selectivity of SPICE and VCP is the presence of oppositely charged residues in CCP domains 2–3 [ 125 , 126 ].…”
Section: Viral Complement Regulatorsmentioning
confidence: 99%